العوامل المدرسية التي تؤدي إلى التسرب المدرسي في ظل التكنولوجيا المعلومات والاتصالات - لوحيدي, فوزي; جلول, أحمد; بن عمارة, اشواق (جامعة الوادي - University of Eloued, 2020)
تعد ظاهرة التسرب المدرسي من المشاكل التي تعاني منها المدرسة في القرن 21، وهي ليست بالظاهرة الجديدة التي تعاني منها التربية والتعليم والمدارس، حيث انتشر بصورة كبيرة بين جميع أوساط التلاميذ وفي مختلف المراحل التعليمية، خاصة بظهور التغيرات والتطورات الحاصلة في مجال تكنولوجيا المعلومات والاتصالات، مما جعل إعادة النظر في العوامل المدرسية وعناصر العملية التعليمية التعلمية، وفق ما تتطلبه مستجدات الحياة وإعادة بلورة سياساته واستراتجياته وخططه، ولهذا تبحث دراستنا عن دور العوامل المدرسية التي قد تؤدي إلى التسرب المدرسي، في ظل المستجدات الحاصلة، وقد تكون في بعض الأحيان سوء العلاقة بين المعلم والتلاميذ وبين الإدارة والتلميذ ولعدم تفهم أوضاعه ومشاكله، أو في المعلم في حد ذاته، أو المنهاج التربوي أو الكتاب المدرسي وغيرها من العوامل التي قد تكون سبباً في مغادرة التلميذ من المدرسة ويتسرب منها.The school dropout phenomenon is one of the problems that the school suffers from in the 21st century, and it is not a new phenomenon that education and schools suffer from, as it has spread widely among all pupils and in various educational stages, especially the appearance of changes and developments in the field of information and communications technology, which Making reconsideration of school factors and elements of the educational learning process, as required by the developments in life and the re-development of its policies, strategies and plans, and this is why our study looks for the role of school factors that may lead to school dropout, in light of the developments taking place, and D be sometimes poor relationship between the teacher and students and between the administration and the student and the lack of understanding of the conditions and problems, or in the teacher itself, or educational curriculum or textbook and other factors that may be the cause of the departure of the student from the school and leaking.
School factors that lead to school dropout in light of information and communication technology
مقال
Keywords: المدرسة ، التسرب المدرسي، العوامل المدرسي; school , school dropout , school factors